Atherosclerotic changes in aorta and coronary arteries at autopsy in North Indian population - Khanna, Kunal; Garg, Varun; Khanagwal, Vijay Pal; Dagar, Tarun; Paliwal, Pramod Kumar; Sen, Rajeev (International Journal of Advances in Medicine, 2019)
Background: Cardiovascular disease (CVD) has become a ubiquitous cause of morbidity and a leading contributor to mortality in most countries. It has emerged as a major health burden worldwide with atherosclerosis being the major cause. Methods: 150 random cases of different age groups brought for postmortem examination in the Department of Forensic Medicine PGIMS, Rohtak. Heart was removed and examined after obtaining the consent of next of the kin of the deceased. Gross macroscopic changes were noted and microscopic changes examination was done and reported by preparation of slides in collaboration with Department of Pathology of the Institute. Results: The study group comprised of mostly males (70%) with mean age of 36.90±13.88 years. Almost half of them were in their third and fourth decade of life. 83 cases were found to have atherosclerosis and 25 of them belonged to the age group 40 to 49 years. 82 % of these cases were of male gender. Histopathological grading carried out displayed that Grade III lesions were maximum (27.5%) followed by grade IV lesions (19.0%) and in no section grade VIII lesions were seen. Conclusion: Atherosclerosis has emerged as a new epidemic affecting at a relatively younger age. This study would help in planning of preventive measures directed at the right population. Clinicians could take measures at an early stage to prevent the progression of the disease and will help forensic pathologists in dealing with opinion regarding cause of death.